BRONCHIAL ASTHMA SUPERVISION AMONG TEENAGERS - N.M. Nenasheva (Union of pediatricians of Russia, 2008)
The article highlights the results of the act test based bronchial asthma supervision evaluation among teenagers and defines the interrelation of the objective and subjective asthma supervision parameters. The researchers examined 214 male teenagers aged from 16 to 18, suffering from the bronchial asthma, who were sent to the allergy department to verify the diagnosis. Bronchial asthma supervision evaluation was assisted by the act test. The research has showed that over a half (56%) of teenagers, suffering from mild bronchial asthma, mention its un control course, do not receive any adequate pharmacotherapy and are consequently a risk group in terms of the bronchial asthma exacerbation. Act test results correlate with the functional indices (fev1), as well as with the degree of the bronchial hyperresponsiveness, which is one of the markers of an allergic inflammation in the lower respiratory passages.Key words: bronchial asthma supervision, act test, teenagers.